2023
DOI: 10.1177/03635465221142320
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sports Activity After Periacetabular Osteotomy: A Qualitative and Quantitative Analysis

Abstract: Background: Patients undergoing periacetabular osteotomy (PAO) for symptomatic developmental dysplasia of the hip are usually young and active with high functional demands. Those who participate in sports seek surgical therapy to resume or maintain sports activities. There is little evidence regarding the postoperative level of activity and the extent to which sports activity changes after PAO both qualitatively and quantitatively. Purpose: The aim of this study was to determine the change in activity level as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Patients could categorize themselves The American Journal of Sports Medicine as (1) between 1 and 3 months, (2) between 3 and 6 months, (3) after .6 months, or (4) no return to sports. 18 Preoperative and postoperative activity levels and hip function were assessed during a routine examination. The activity level was determined using the UCLA activity scale.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients could categorize themselves The American Journal of Sports Medicine as (1) between 1 and 3 months, (2) between 3 and 6 months, (3) after .6 months, or (4) no return to sports. 18 Preoperative and postoperative activity levels and hip function were assessed during a routine examination. The activity level was determined using the UCLA activity scale.…”
Section: Data Collectionmentioning
confidence: 99%
“…For simplification, a list of common sports (cycling, alpine skiing, fitness training, tennis, basketball, soccer, handball, volleyball, hiking, golf, long walks, Nordic walking, running/jogging) was provided. 18 Sports not included in the list were recorded by free-text answers. Furthermore, the option of ''no sports'' was listed, and multiple choices were possible.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…although overall sports activity rate increases (including in frequency and duration), participation in high-impact sports decreases, and one-tenth report starting new sports 76 .…”
Section: Athletic Trainer and Return To Playmentioning
confidence: 99%
“…A more recent systematic review of 6 studies and 341 patients undergoing PAO found that postoperative participation in low-, moderate-, and high-impact sports was observed with greater than 70% RTP in competitive athletes 75 . One study found that although overall sports activity rate increases (including in frequency and duration), participation in high-impact sports decreases, and one-tenth report starting new sports 76 .…”
Section: Clinical Scenariomentioning
confidence: 99%